Distinguishing resistances of transgenic sugarcane generated from RNA interference and pathogen‐derived resistance approaches to combating sugarcane mosaic virus - Weny Nailul Hidayati; Retnosari Apriasti; Hardian Susilo Addy; Bambang Sugiharto (Universitas Gadjah Mada, 2021)
Sugarcane mosaic virus (SCMV) is a causative agent that reduces growth and productivity in sugarcane. Pathogen‐derived resistance (PDR) and RNA interference (RNAi) are the most common approaches to generating resis‐ tance against plant viruses. Two types of transgenic sugarcane have been obtained by PDR and RNAi methods using a gene‐encoding coat protein (CP) of SCMV (SCMVCp). This research aimed to distinguish resistance of the two transgenic sugarcanes in combating SCMV through artificial viral inoculation. The experiment was conducted using transgenic sugar‐ cane lines validated by PCR analysis. Insertion of gene‐encoding CP in the transgenic lines was confirmed by amplification of 702 bp of DNA fragment of SCMVCp. After viral inoculation, mosaic symptoms appeared earlier, at 21 days post inoculation (dpi) in PDR transgenic lines, but was at 26 dpi in RNAi transgenic lines. Symptom observation showed that 77.8% and 50% of the inoculated plants developed mosaic symptoms in PDR and RNAi transgenic lines, respectively. RT‐PCR analysis revealed that the nuclear inclusion protein b (Nib) gene of SCMV was amplified in the symptomatic leaves in plants classified as susceptible lines. Immunoblot analysis confirmed presence of viral CP with a molecular size of 37 kDa in the susceptible lines. Collectively, these results indicated that the RNAi approach targeting the gene for CP effectively produces more resistance against the SCMV infection in transgenic sugarcane compared to the PDR approach.